ANALYSIS OF FACTORS AFFECTING PALM OIL PRODUCTION IN PTPN IV REGIONAL II KEBUN MELATI, PEGAJAHAN DISTRICT, SERDANG BEDAGAI DISTRICT - Permata Banowati; Tuty Ningsih (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to: (1) identify production factors that influence palm oil production at PTPN IV Regional II Kebun Melati; (2) analyze the influence of labor, rainfall, fertilizer, and herbicide partially or simultaneously on Fresh Fruit Bunches (FFB) production; and (3) determine the most dominant production factors. The study was conducted at PTPN IV Regional II Kebun Melati, Pegajahan District, Serdang Bedagai Regency, in January–March 2026, using 60 monthly time series data for the 2021–2025 period. Cobb -Douglas production function analysis was used with the help of SPSS software. All classical assumption tests (normality, autocorrelation, heteroscedasticity, and multicollinearity) were met. The results of the study showed that: (1) simultaneously, labor, rainfall, fertilizer, and herbicide had a significant effect on FFB production (F-count = 66.684, sig. = 0.000); (2) partially, rainfall (sig. = 0.000), fertilizer (sig. = 0.001), and herbicide (sig. = 0.003) have a real and positive effect, while labor (sig. = 0.117) has no significant effect; (3) herbicide is the most dominant production factor with an elasticity coefficient of 0.690; and (4) the Return to Scale value of 1.496 indicates a condition of increasing returns to scale. The coefficient of determination (R²) value of 0.914 indicates that 91.4% of the variation in FFB production can be explained by these four input variables.